2019
DOI: 10.21203/rs.2.15580/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Satisfaction of Caretakers on Community Based Newborn Care and Its Predictors in Boloso Sore District, Southern Ethiopia

Abstract: Background: A community based newborn care was very important to the survival of newborns. The program is primarily provided by Health Extension Workers. However, the quality of the care in relation to caretakers’ satisfaction has not been adequately documented. Therefore the aim of this study was to assess satisfaction of caretakers on Community-Based Newborn Care and its predictors in Boloso Sore District in South Ethiopia.Methods: A community based cross-sectional study design was done on 426 caretakers wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…As stated by most of the participants PNC performance is very poor due to the fact that PNC is being given at home through home visits by HEWs which is very difficult for them as they might have multiple duties, long distance of houses from health posts and their negligence due to poor supervision. Similarly, previous studies reported low postnatal home visits by HEWs, 26,28 and another study in Ethiopia shows a distance of more than 30 minutes' walk was associated with a lower level of health post utilization of maternal and child health services and would mean that HEWs visits to households was based on the distance of the houses from the health posts. 12 It is believed that CHWs can identify pregnant women and newborns in need of medical attention and care, promote and encourage appropriate care seeking, and provide counselling and support for home care practices across the periods of pregnancy, newborn, and childhood.…”
Section: Performance Of Hews Regarding the Servicesmentioning
confidence: 69%
See 2 more Smart Citations
“…As stated by most of the participants PNC performance is very poor due to the fact that PNC is being given at home through home visits by HEWs which is very difficult for them as they might have multiple duties, long distance of houses from health posts and their negligence due to poor supervision. Similarly, previous studies reported low postnatal home visits by HEWs, 26,28 and another study in Ethiopia shows a distance of more than 30 minutes' walk was associated with a lower level of health post utilization of maternal and child health services and would mean that HEWs visits to households was based on the distance of the houses from the health posts. 12 It is believed that CHWs can identify pregnant women and newborns in need of medical attention and care, promote and encourage appropriate care seeking, and provide counselling and support for home care practices across the periods of pregnancy, newborn, and childhood.…”
Section: Performance Of Hews Regarding the Servicesmentioning
confidence: 69%
“…However, a study conducted in Wolaita zone, southern Ethiopia, shows only half of the studied caretakers were satisfied with HEWs services indicating low acceptance. 26 Our findings explored that MNCH and CBNC services provided by HEWs are highly valued by the community and indicate a shift of strategy to focus on other factors like health system readiness, coordination, and organization for low performance of the program.…”
Section: Acceptance Of the Services Provided By Hews By The Communitymentioning
confidence: 83%
See 1 more Smart Citation
“…Data were collected through face-to-face interviews using structured questionnaires. Data collection instrument was developed after reviewing related relevant literatures [10,12,16,17,19,24]. The question mainly consisted of close-ended questions addressing socio-demographic characteristics of respondents, client-provider interaction, hospital-related factors, and clinical and admission factors.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…It is influenced by a variety of factors, including societal norms, the context in which health care is delivered, the need for and value of caregivers, and personal experiences [13,15,16]. Expectations, educational level, health, ability to receive medical care, knowledge, and other psychological factors all play a role [17][18][19][20].…”
mentioning
confidence: 99%